Therapeutic potential of alpha-ketoglutarate against acetaminophen-induced hepatotoxicity in rats - Lalita Mehra; Yasha Hasija; Gaurav Mittal (Wolters Kluwer Medknow Publications, 2016)
Objective: Alpha-ketoglutarate (α-KG) is a cellular intermediary metabolite of Krebs cycle, involved in energy metabolism, amino acid synthesis, and nitrogen transport. It is available over-the-counter and marketed as a nutritional supplement. There is a growing body of evidence to suggest that dietary α-KG has the potential to maintain cellular redox status and thus can protect various oxidative stress induced disease states. The aim of the present study was to investigate the hepatoprotective role of α-KG in acetaminophen (APAP) induced toxicity in rats. Materials and Methods: Animals were divided into three groups of six animals each. Group I (Vehicle control): Normal Saline, Group II (APAP): A single intraperitoneal injection of 0.6 g/kg, Group III (APAP + α-KG): APAP as in Group II with α-KG treatment at a dose of 2 g/kg, orally for 5 days. Then the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) with oxidative stress markers including malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and histopathology were analyzed. Results: The results indicate that APAP caused significant elevations in ALT, AST, ALP, and MDA levels, while GSH, SOD, and CAT were significantly depleted while co-administration of α-KG showed a significant (P < 0.05) reduction in the severity of these damages. Histologically, the liver showed inflammation and necrosis after APAP treatment, which were significantly restored with co-administration of α-KG. Conclusion: These results indicate the possible therapeutic potential of α-KG in protecting liver damage by APAP in rats.